Pengaruh Sistem Absensi Fingerprint Terhadap Kinerja Karyawan Pada PT. Deltacomsel Indonesia - Hylenarti Hertyana (Universitas Bina Sarana Informatika, 2016)
Applying Fingerprint attendance system can help companies to control employee work time more efficiently. Results The response from the respondents on the output performance of employees responded well because the average value of the entire statement is at 4.04 which is in the interval from 3.40 to 4.19. Meanwhile, the output performance of employees at PT. Deltacomsel Indonesia can be said to be good for the average value of the entire statement is at 4.04 which is in the interval from 3.40 to 4.19. Respondents to the utilization of Fingerprint Time Attendance System at PT. Deltacomsel Indonesia is good, with an overall average score of 3.97 which is in the interval from 3.40 to 4.19. Fingerprint Time Attendance System influence on the performance of employees at PT. Deltacomsel Indonesia is still very low. It can be seen Calculation of the coefficient of determination is done by squaring the correlation coefficient (rs) so that the correlation coefficient of 0.89%. This figure means 0.89% of employee performance is affected by Fingerprint Time Attendance System and the remaining 99.11% influenced by factors other than the fingerprint attendance system.. Keywords: attendance system, fingerprint, performance